1997
DOI: 10.1128/aem.63.5.1771-1776.1997
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of polychlorinated biphenyl-dechlorinating microorganisms in contaminated sediments

Abstract: The growth dynamics of polychlorinated biphenyl (PCB)-dechlorinating microorganisms were determined for the first time, along with those of sulfate reducers and methanogens, by using the most-probable-number technique. The time course of Aroclor 1248 dechlorination mirrored the growth of dechlorinators; dechlorination ensued when the dechlorinating population increased by 2 orders of magnitude from 2.5 ؋ 10 5 to 4.6 ؋ 10 7 cells g of sediment ؊1 , at a specific growth rate of 6.7 day ؊1 between 2 and 6 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
1
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 26 publications
(44 reference statements)
6
58
1
1
Order By: Relevance
“…Chem. 18, 1999 2701 that observed in BES-free sediments, the pattern with higher dilution inocula was similar to that observed in BES-amended sediments [19]. These results suggest that the methanogenic population involved in dechlorination may have a low affinity for the PCB mixture and that its size is relatively small.…”
Section: Interactions Of Pcb Dechlorinatorssupporting
confidence: 65%
See 3 more Smart Citations
“…Chem. 18, 1999 2701 that observed in BES-free sediments, the pattern with higher dilution inocula was similar to that observed in BES-amended sediments [19]. These results suggest that the methanogenic population involved in dechlorination may have a low affinity for the PCB mixture and that its size is relatively small.…”
Section: Interactions Of Pcb Dechlorinatorssupporting
confidence: 65%
“…1). The fact that the number of sulfate reducers in inhibitor-free cultures was about one to two orders of magnitude higher than those of methanogens or dechlorinators indicates that sulfate reducers were a dominant population under these experimental conditions, as was the case in our earlier study [14]. Neither dechlorination nor growth of dechlorinators was observed in sediments amended with both inhibitors.…”
Section: Interactions Of Pcb Dechlorinatorssupporting
confidence: 42%
See 2 more Smart Citations
“…Therefore, if biomass was also proportional to PCB concentrations, the linear pattern could drastically change. Using the most-probable-number technique, we recently demonstrated that the growth of PCB-dechlorinating microorganisms requires the presence of PCBs [23]. This finding suggests that the biomass of dechlorinators may also vary with PCB concentration.…”
Section: Discussionmentioning
confidence: 99%